PENGARUH PEMAHAMAN PERPAJAKAN, SANKSI PAJAK DAN KEADILAN PAJAK TERHADAP PENGGELAPAN PAJAK MENURUT PERSEPSI MAHASISWA - Laisya Fauziah Ramadhani; Wahyu Nurul Hidayati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the influence of tax knowledge, tax sanctions, and tax fairness on tax evasion based on students' perceptions. This is a quantitative study employing purposive sampling. The study population consists of 8th-semester undergraduate Accounting students (Regular Class A) specializing in Taxation at Pamulang University. Purposive sampling was used to select a sample of 156 students. Data analysis techniques included descriptive statistics, data quality tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing using SPSS version 32. The results indicate that tax knowledge, tax sanctions, and tax fairness simultaneously have a significant effect on tax evasion. Individually, tax knowledge, tax fairness, and tax sanctions each have a significant effect on tax evasion according to the students' perceptions.